2019
DOI: 10.1039/c8mh01298a
|View full text |Cite|
|
Sign up to set email alerts
|

Hydrogel nanotubes with ice helices as exotic nanostructures for diabetic wound healing

Abstract: Hydrogel nanotubes with ice helices entrapped within their internal conduits are a promising material for diabetic wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…The prepared hydrogel samples were applied at the wound sites as our previously reported study. 33 Figure 5 shows the images of the rat skin wounds taken at different time intervals after treating with a marketed standard, pDMAEMA–HA hydrogel, and pDPi-DMAEMA–HA hydrogel. The control group (without treatment) was also included with no sign of inflammation and infection occurring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prepared hydrogel samples were applied at the wound sites as our previously reported study. 33 Figure 5 shows the images of the rat skin wounds taken at different time intervals after treating with a marketed standard, pDMAEMA–HA hydrogel, and pDPi-DMAEMA–HA hydrogel. The control group (without treatment) was also included with no sign of inflammation and infection occurring.…”
Section: Resultsmentioning
confidence: 99%
“… 35 , 36 Our previously reported study demonstrated that hydrogel nanotubes exhibited unique biocompatibility and helped in the rapid establishment of wound barrier properties with concomitant cell proliferation guided by the provisional matrix mimicking an extracellular matrix niche, which support permissive milieu for vascular sufficiency with a well-proliferated fibroblast at the wound bed. 33 In addition, cell migration and proliferation efficacy in vitro and contractile force generated by HA could be the reason of the excellent healing performance of these hydrogels. 33 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Hydrogels are highly water-swollen networks made of hydrophilic polymers with tunable mechanical, physical and chemical characteristics. 33–35 The high-water content of hydrogels makes it easier and faster for nutrient and waste transport in the network. 36 Compared with other culture systems, most hydrogels can be formed under mild conditions and can be modified to possess the desired properties such as cell adhesion, 37 viscoelastic features 31,38 and degradability.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular response promotes phagocytosis and removal of dead tissue to promote the generation of healthy tissues. Remodeling phase, in partial-thickness burns proliferation phases, starts by reepithelization, in the form of keratinocyte migration from skin appendages with few hours of injury, which usually requires 5-7 d for complete wound coverage, followed by the formation of basement membrane zone between dermis and epidermis [3]. Angiogenesis and fibrogenesis promote the reconstruction of the dermis, followed by maturation of graft or scar.…”
Section: Introductionmentioning
confidence: 99%